Diagnostic utility of a one-item question to screen for depressive disorders: results from the KORA F3 study - Blozik, Eva; Scherer, Martin; Lacruz, Maria E; Ladwig, Karl-Heinz (BMC family practice, 2013)
Background Screening for depressive disorders in the general adult population is recommended, however, it is unclear which instruments combine user friendliness and diagnostic utility. We evaluated the test performance of a yes/no single item screener for depressive disorders (“Have you felt depressed or sad much of the time in the past year?”) in comparison to the depressive disorder module of the Patient Health Questionnaire (PHQ-9). Methods Data from 3184 participants of the population-based KORA F3 survey in Augsburg/ Germany were used to analyse sensitivity, specificity, ROC area, positive likelihood ratio (LR+), negative likelihood ratio (LR-), positive predictive value (PPV), and negative predictive value (NPV) of the single item screener in comparison with “depressive mood” and “major depressive disorder” defined according to PHQ-9 (both interviewer-administered versions). Results In comparison to PHQ-9 “depressive mood”, sensitivity was low (46%) with an excellent specificity (94%), (PPV 76%; NPV 82%; LR + 8.04; LR- .572, ROC area .702). When using the more conservative definition for “major depressive disorder”, sensitivity increased to 83% with a specificity of 88%. The PPV under the conservative definition was low (32%), but NPV was 99% (LR + 6.65; LR- .196; ROC area .852). Results varied across age groups and between males and females. Conclusions The single item screener is able to moderately decrease post-test probability of major depressive disorders and to identify populations that should undergo additional, more detailed evaluation for depression. It may have limited utility in combination with additional screening tests or for selection of at-risk populations, but cannot be recommended for routine use as a screening tool in clinical practice.